The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fphys.2020.00582
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Control of the Heart and Its Clinical Impact. A Personal Perspective

Abstract: This essay covers several aspects of the autonomic control of the heart, all relevant to cardiovascular pathophysiology with a direct impact on clinical outcomes. Ischemic heart disease, heart failure, channelopathies, and life-threatening arrhythmias are in the picture. Beginning with an overview on some of the events that marked the oscillations in the medical interest for the autonomic nervous system, our text explores specific areas, including experimental and clinical work focused on understanding the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 163 publications
(228 reference statements)
0
27
0
Order By: Relevance
“…Indeed, the 2UV% was significantly higher in POST than PRE and this finding is compatible with a more active vagal control. Remarkably, changes of HRV markers occurred in absence of modifications of µ, thus supporting their full link with variations of the state of the autonomic nervous system (Zaza and Lombardi, 2001;Bauer et al, 2017;Boyett et al, 2019;La Rovere et al, 2020). Modifications of the autonomic control depend on type, duration, and intensity of exercise (Stanley et al, 2013;Michael et al, 2017).…”
Section: Post Symbolic Markers Are Significantly Different From Pre Smentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, the 2UV% was significantly higher in POST than PRE and this finding is compatible with a more active vagal control. Remarkably, changes of HRV markers occurred in absence of modifications of µ, thus supporting their full link with variations of the state of the autonomic nervous system (Zaza and Lombardi, 2001;Bauer et al, 2017;Boyett et al, 2019;La Rovere et al, 2020). Modifications of the autonomic control depend on type, duration, and intensity of exercise (Stanley et al, 2013;Michael et al, 2017).…”
Section: Post Symbolic Markers Are Significantly Different From Pre Smentioning
confidence: 69%
“…Despite the small magnitude of the RR changes, the percentage of highly variable RR patterns (i.e., 2UV%) significantly raised during PLATEAU compared to PRE sequences, thus suggesting a remarkable vagal modulation. The dependence of σ 2 and HFa power on μ ( Boyett et al, 2019 ), affecting mainly the HRV markers expressed in absolute units ( Zaza and Lombardi, 2001 ; La Rovere et al, 2020 ), might have prevented the full comprehension of the relevance of the vagal control during PLATEAU, thus stressing the limits of time and frequency domain markers in this context. Conversely, since symbolic markers are normalized by definition between 0 and 100, they are not sensible to this bias ( Zaza and Lombardi, 2001 ; La Rovere et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of estimating the complexity of QT variability is relevant because it was suggested that a limited complexity of the QT variability might lessen the arrhythmic risk [9,10]. In the present study we hypothesize that, despite the decrease of the RR variability irregularity during sympathetic activation, QT variability complexity remains high and this behavior is owing to the increase of the complexity of the neural actions genuinely modifying QT [11].…”
Section: Introductionmentioning
confidence: 69%
“…is condition is quite common for older people, but its prevalence can vary for different groups, with older community dwellers having the lowest rate, long-term care residents having the highest, and hospitalized older adults falling in between [11]. e evolution of cardiovascular control with age via several HRV markers has been reported extensively in the literature [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several HRV indices have been used to assess the variation of ANS modulations, for example, systolic arterial pressure, Shannon entropy, low-frequency power (LF), high-frequency power (HF), and LF/HF ratio [12][13][14][15]. Since the ANS is characterized by a dynamic balance between the PNS and the SNS activities-which originate via multiple HRV regulatory mechanisms, several indices of HRV can thus be used to monitor the ANS modulations.…”
Section: Introductionmentioning
confidence: 99%